Basic Research on Neuronal Activation Induced by Intradiscal Pain Stimulation into Degenerative ?Intervertebral Disc Using Capsaicin. (May 2014) - Orita, S.; Nishiori, H.; Yamauchi, K.; Sakuma, Y.; Kubota, G.; Oikawa, Y.; Inage, K.; Sainoh, T.; Sato, J.; Fujimoto, K.; Takahashi, K.; Ohtori, S.
Introduction: Previously, it was reported that pain perception is related to not only DRG but also to the reaction of the central nervous system; however, the reaction of the dominant nervous system to pain stimulus in the intervertebral discs is unknown. The purpose of this research was to verify the mechanism of reaction of the nervous system, which controls the intervertebral discs, using chemical pain stimulus. Materials and Methods: We used 6-week-old Sprague Dawley rats, and injected 20 µL capsaicin solution, which contains 2% Fluoro-Gold (FG), into the L5/6 intervertebral disc. FG is an antidromic neuronal tracer. Seven days after injection, we prepared perfusion fixation of the rats and extracted DRGs from L1 to L6 along with the lumbar enlargement of spinal cord. At the DRG, we detected CGRP, which is a nociceptive pain-related protein, by immunostaining, and measured the distribution of the expression. At the lumbar enlargement of the spinal cord, we detected Iba1, which is a marker for pain stimulus-activated micro glia, and compared Iba 1 expression in the capsaicin group and vehicle group, in which we injected only 20 µL saline solution (each is n = 5). Results: The rate of distribution of CGRP positive cells in the FG positive rats was highest at the L2 DRG, and the rate was higher in the capsaicin group (54.9%) than in vehicle group (27.1%), with a statistically significant difference ( p < 0.05). The number of Iba1 positive micro glia cells per 1.4 × 10 mm 2 was also larger in the capsaicin group (31.7 cells) than in the vehicle group (14.8 cells), with a statically significant difference ( p < 0.05) Conclusion: The results of this experiment suggested that the chemical stimulus to the L5/6 intervertebral disc resulted in an elevated CGRP expression that caused pain around the L2 DRG area, and the mechanism of pain perception is strongly related to the activation of microglia at the posterior horn of the spinal cord. Disclosure of Interest None declared